Comparison of serum zinc in children younger than 5 years old with febrile convulsion, children with seizures without fever and normal children - A, Ali Vahidi; Torabinejad, Mohammad; Shamspour, Marayam; Golmohammadi, Niloofar; Heidari, Mohammad (International Journal of Research in Medical Sciences, 2017)
Background: Febrile seizures are the most common seizure disorder in children and have a good prognosis. Many theories about the role of neurotransmitters and trace elements in serum and cerebrospinal fluid are introduced as the pathogenesis of febrile seizures. Among these elements, the element can be noted. The purpose of this study to comparison of serum zinc in children younger than 5 years old with febrile convulsion, children with seizures without febrile and normal children. Methods: In this study, 180 children were studied in three groups. 60 children with seizures without fever and 60 children with febrile convulsions admitted to hospital and 60 healthy children without a history of seizures. Afzalipour who were referred to health centers in the city of Kerman. Serum zinc levels in all three groups were measured by atomic absorption spectrophotometry. Results: The mean serum zinc levels in children with febrile seizures in this investigation was 48.4 µg/dl, compared with the other two tense children without fever (64.61 µg/dl) and healthy children (67.33 µg/dl) was significantly lower. Conclusion:Results of this study showed reduced serum zinc levels during febrile seizure. The need for continued research on surface tension in febrile children over several months is recommended.